University-owned Patents in West and East Germany and the Abolition of the Professors' Privilege - Sidonia von Ledebur (Philipps-University Marburg, Department of Geography, 2009)
This paper analyses the development of universities' patent applications in Germany before and after the abolition of the 'professors' privilege' in 2002. By means of a database with all patent applications of German universities with professors among the inventors (1990-2006), systematic changes in the trend are investigated. There are contrasts in the patenting patterns of universities with or without long patenting experience. A structural break at the point of the new legislation is found only for universities without patent activities in the past. This indicates the importance of collecting patenting experience and that the amount of patents is path-dependent.
Keywords: O34; O38; L31; 330; university patenting; Germany; technology transfer; professors' privilege